Sistem Informasi Desa Berbasis Web Pada Desa Sungai Benuh Kecamatan Sadu - Sutriani, Novi Alia; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2021)
The government system in the village of Sungai Benuh currently still conventional in terms of internal administration and public services. In the internal part, the frequently problems experienced are some cases like delay in publishing the letters because its validation process, archiving the data and documents likely to get misplaced or lost, the activity is not documented and frequently delays in the delivery of the report. While in public services the problem is the data of some people not updated even there is some don’t have it, the informations is difficult to access and there is no transparency regarding the government system. The purpose of this research is to design a information system to help the Sungai Benuh village government and the community according to their needs. The Data collection was done by interviewing and observation. The information system design method using prototype with system modeling tools, called UML. The output or result obtained from this research is a web-based information system design for Sungai Benuh Village for internal administration which consists of managing village profiles, population data, letters, inventory, activities, giving approval, managing personnel data and managing financial reports. Meanwhile, public services consist of an information menu, submissions for population data creation, correspondence and progress status.